Development of minimized mixing molecular orbital method for designing organic ferromagnets. Issue 16 (22nd April 2015) - Zhu, Xun; Aoki, Yuriko
<x xml:space="preserve">Abstract</x> Predicting the high spin stability of organic radicals correctly for designing organic ferromagnets remains a significant challenge. We have developed a method with an index (Lmin) for predicting the high spin stability of conjugated organic radicals at the restricted open‐shell Hartree–Fock level. Unitary transformations were performed for localizing the coefficients of nonbonding molecular orbitals, and subsequently the localized coefficients were used to calculate Lmin that indicates the high spin stability of conjugated organic radicals. This method can be combined with the elongation method to treat huge high spin open‐shell systems. Thus, this method is useful for designing organic ferromagnets. © 2015 Wiley Periodicals, Inc.